2010
DOI: 10.1308/003588410x12664192075738
|View full text |Cite
|
Sign up to set email alerts
|

Recognising anaemia and malnutrition in vascular patients with critical limb ischaemia

Abstract: INTRODUCTION Anaemia is a common problem in surgical patients. Patients with critical limb ischaemia (CLI) suffer chronic inflammation, repeated infection, require intervention, and can have a protracted hospital stay. The aims of this study were to assess anaemia and nutritional status in patients presenting with CLI. PATIENTS AND METHODS Two observational studies were undertaken, initially a retrospective series of 27 patients with CLI. Patient demographics, clinical details, transfusion status and in-patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Fifty three percent of our patients with CLI had anaemia on admission. This is in line with a study published by Shah M. et al who found that 56% of patients admitted to a tertiary hospital in the United Kingdom for CLI had anaemia [2]. Most of our patients with anaemia as a comorbidity on admission had only mild anaemia (mean 113 g/L ±SD 14).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fifty three percent of our patients with CLI had anaemia on admission. This is in line with a study published by Shah M. et al who found that 56% of patients admitted to a tertiary hospital in the United Kingdom for CLI had anaemia [2]. Most of our patients with anaemia as a comorbidity on admission had only mild anaemia (mean 113 g/L ±SD 14).…”
Section: Discussionsupporting
confidence: 92%
“…It may also impair other vital organ functions and the immune response resulting in increased mortality. Musallam et al recently described mild anaemia as an independent predictor of increased thirty days morbidity and mortality in a large cohort of patients undergoing major non-cardiac surgery [2]. The unadjusted mortality rate in patients who had any degree of anaemia was six times that of those who did not have pre-operative anaemia [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-NLR was identified as an independent predictive factor of amputation in CLI patients who did not undergo surgery. CLI patients usually suffer from malnutrition ( 20 ) due to sleeplessness and lack of appetite, leading to chronic ischemic pain. Moreover, variable albumin is a crucial index for evaluating a patient's nutritional condition, and hypoproteinemia is a risk factor for amputation in PAD ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Patients with peripheral arterial disease (PAD) are prone to anemia of chronic disease. This is likely a consequence of repeated infection and the inflammatory response associated with critical limb ischemia, 4 while iron-deficiency anemia may reflect poor nutrition in others.…”
Section: Introductionmentioning
confidence: 99%